Produtividade da mão de obra na execução de sistemas prediais elétricos e de comunicação - Corsini, Thomaz de Assumpção (Universidade Federal de São Carlos, 2016)
Labor productivity indicators are important for several reasons, among which can be cited: a more accurate composition of budgets; the establishment of production goals; and to determine the correct work team size. Several works have quantified labor productivity of construction services, and in this context, there is a noticeable lack of works that deal with building systems execution, particularly, the ones related to power and communication systems. This work has the objective of analyzing labor productivity in the execution of those systems and is based in the Factor Model. To accomplish that, three different tasks in five multistory buildings were measured: electrical infrastructure in wall; electrical infrastructure in concrete slab; and electrical wiring. At the same time, some context and content factors that are likely to influence labor productivity were pointed out. Among the analyzed tasks, the one that presented the best productivity was the electrical wiring on site D (Cumulative productivity = 0.019 Wh/m), while the worst value (Cumulative productivity = 0.080 Wh/m) was detected in electrical infrastructure in concrete slab on Site B. Among the influencing factors identified, there are indications that the type of contract firmed with workers influenced labor productivity, with better results where the workers were subcontracted. The labor productivity results obtained are much better than those presented in reference manuals, indicating the necessity of additional works with the analysis of a larger number of cases.
Keywords: Produtividade da mão de obra; Composição dos serviços; Sistema predial elétrico e de comunicação; Labor productivity; Task composition; Electrical and communication building systems; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL